Counseling methodologies for the ethnic minorities in the Philippines - Rosales, Lily Rosquieta
The study concerned itself with the various counseling methodologies (therapeutic approaches) which may be used with the following people: the mountain Tinggians of Abra, the Bontoc Igorots of Mountain Province, and the Ibanags of Mongol descent of the Cagayan Valley. A sampling of men, women, and youth was made. The men's ages ranged fro 35 to 74; the women's ages ranged from 25 to 80; the youth's ages ranged from 15 to 20. The approaches used were based on Dr. Burl Gilliland's classification.
Keywords: Minorities -- Counseling of -- Philippines